ANALISIS IMPLEMENTASI RAPOR PENDIDIKAN DALAM PENGELOLAAN PEMBIAYAAN DI SD NEGERI KALONGAN 02 - Qun Firmani Lestari; Nugraheni, Ardhina Maya; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the implementation of the Kalongan 02 State Elementary School using education report card data to plan education financing. The main focus of the research is whether the school has succeeded in using education report card data in planning financing at the Kalongan 02 State Elementary School. This research uses qualitative methods, meaning the researcher conducted interviews, directly observed activities at the school, and collected various documents. The results show that although schools have been able to find problems from student learning outcomes reports, in planning financing management, schools have not fully used this data. For example, even though data shows that students are still weak in literacy and numeracy skills, and school facilities do not fully facilitate inclusive students, the budget created is not fully aimed at overcoming these problems. From the results of this research, researchers recommend that schools be more careful in planning financing, analyze data in more depth, and involve all interested parties. This research emphasizes the importance of using data in managing schools and provides suggestions for improving the quality of education by managing school fees better.